INSTAGRAM FOR MARKETING COMMUNICATION ART EVENTS DURING COVID-19 (CASE STUDY OF 2021 BIENNALE JOGJA IN YOGYAKARTA, INDONESIA) (Journal of Creative Industry and Sustainable Culture, 2023)
In 2021 Indonesian government policy enforced restriction towards community activities, to prevent the Covid-19 spread. This policy affected many aspects, includes art events. This article aims to discuss the social media strategy by 2021 Biennale Jogja. That was the first international art event held hybrid (online and offline) in Yogyakarta, Indonesia, during the Covid-19. Focus on this article was on the Instagram for marketing communication, because Instagram become the important tools for marketing communication. Methods: descriptive qualitative, data collecting techniques were interview with the 2021 Biennale Jogja organizer. As the data triangulation, we use the visitor responses by observing the Instagram analytics and trends, followed interview with visitors. Results grouped into four elements of social media marketing. First created buzz by spreading any information through Instagram to build engagement, include with the visitor who could not came to the venue. Second social media plan, by identified the target audience and their characteristics. Third was developed relationship with the audience by use the non-formal language in posted materials, the particular hashtags, and make content upload schedule. Fourth was analysed the data collected as evaluation by observed the number of social media reach, engagement, and followers during the event. To attract visitors’ attention, the organizer planned the theme such as information related to the entertainment, education about the artworks, and information about the procedure to visitor who want attend to the venue. Organizer posted different kind of message in the morning, afternoon,and evening. Organizer also created the visual identity for 2021 Jogja Biennale by use orange as the main colour, and blue, purple, and white as the additional colour.